2013
DOI: 10.1371/journal.pone.0054718
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Brachial Artery Vasoreactivity in Elite Power Athletes and Age-Matched Controls

Abstract: Elite endurance athletes typically have larger arteries contributing to greater skeletal muscle blood flow, oxygen and nutrient delivery and improved physical performance. Few studies have examined structural and functional properties of arteries in power athletes.PurposeTo compare the size and vasoreactivity of the brachial artery of elite power athletes to age-matched controls. It was hypothesized brachial artery diameters of athletes would be larger, have less vasodilation in response to cuff occlusion, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Twenty-two studies comprised male subjects, three studies comprised female subjects (23,32,44), and four studies comprised female and male subjects (37,56,60 (20,36,37,59). Arterial endothelial function.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-two studies comprised male subjects, three studies comprised female subjects (23,32,44), and four studies comprised female and male subjects (37,56,60 (20,36,37,59). Arterial endothelial function.…”
Section: Resultsmentioning
confidence: 99%
“…As for the duration of blood flow occlusion, 23 studies used a 5-min period, whereas six studies reported periods between 4 and 5 min (1,23,27,44,50,56). Peak brachial diameter after cuff deflation (i.e., during hyperemia) was determined via continuous ultrasound scan in 20 studies (1,3,(12)(13)(14)20,27,36,40,49,50,59,60) and single time point(s) ultrasound scan in seven studies (23,29,32,(44)(45)(46)56), and one study did not report such information (37). Time to peak brachial diameter after cuff deflation was reported in one study (3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that peripheral vascular conductance during submaximal exercise may not be increased in ATH (Fleg et al, 1994 ; Carrick-Ranson et al, 2014 ) suggests that enhanced arterial dilator function interacts with increased arterial constrictor function and/or sympathetic constrictor drive. In this respect, increased both arterial constrictor function and sympathetic (re)activity have been observed in ATH (Furlan et al, 1993 ; Welsch et al, 2013 ). Seemingly, the antagonism between dilator and constrictor forces may be futile unless associated with a more efficient perfusion in that part of the cardiac output is diverted from tissue with low oxygen demand toward active skeletal muscle.…”
Section: The Unknown Optimal Dilator-constriction Balancementioning
confidence: 98%
“…The controversy arose as to whether vasodilator function was enhanced in ATH compared with untrained healthy peers (Green et al, 2013 ). This contention was justified by the conflicting report of decreased (Green et al, 2011 ; Phillips et al, 2011 ) and normal (Franzoni et al, 2005b ; Moe et al, 2005 ; Naylor et al, 2006 ; Ballard et al, 2008 ; Rognmo et al, 2008 ; Nualnim et al, 2011 ; Phillips et al, 2011 ; Rowley et al, 2012 ; Agrotou et al, 2013 ; Green et al, 2013 ) but also increased (Jensen-Urstad et al, 1999 ; Rywik et al, 1999 ; Rinder et al, 2000 ; Franzoni et al, 2005b ; Kasikcioglu et al, 2005 ; Rickenlund et al, 2005 ; Tanriverdi et al, 2005 ; Galetta et al, 2006 ; Hagmar et al, 2006 ; Walther et al, 2008 ; Florescu et al, 2010 ; Nualnim et al, 2011 ; Welsch et al, 2013 ) flow-mediated dilation (FMD), a common index of conduit artery dilator function, in ATH vs. age-matched controls. Likewise, the evidence on resistance artery dilator function was apparently heterogeneous (Green et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%